A Qualitative Study on the Consequences of Intensive Working. (27th April 2017) - Kirrane, Melrona; Breen, Marianne; O'Connor, Cliodhna
Abstract : The nomological network of intensive working, or 'workaholism', is unclear. Taking a theoretically driven social constructivist approach, anchored in the field of human resource development (HRD), this study sought to explore how male intensive workers understand the consequences of their work patterns with respect to the experience of satisfaction and dissatisfaction in the work and nonwork domains. Deploying an interpretivist paradigm, data from 30 interviews were analyzed. These comprised 10 people who construed themselves as intensive workers, a coworker of each intensive worker, and 10 moderate workers. Each interview was analyzed using discourse analysis techniques. Intensive workers readily described the satisfaction they experienced from their work. Coworkers corroborated these accounts. Many experiences of dissatisfaction among intensive workers were readily offset against gains from intrinsic pleasure in the work or else rationalized. Data from coworkers suggested that intensive workers were both inspirational and troubling colleagues who unwittingly impaired their own career progress. Comparative data from moderate workers further illuminated the consequences of intensive work patterns. This study contributes to theories of intensive work by highlighting the variegated nature of the consequences of intensive working. Understanding how these work patterns are justified and maintained is a critical starting point to support HRD professionals in addressing the consequences that ensue. Such insights have implications for the design and development of organizational policies and procedures that have repercussions for workers' lives.